The arts of the Japanese Sword - Robinson, B. W. (Faber and Farber, 1961)
The subject of the Japanese sword, with its continuous history of some 1,500 years, is a vast one; the names of over 12,000 swordsmiths and 3,000 makers of word-furniture are known and recorded, and the different styles and schools they represent are legion. The most comprehensive Japanese treatise on the whole subject runs to 25 volumes of 5,000 pages, and is the work of more than seven different authorities.